Evaluation of the Use of E-learning in Indonesian Language Learning at Stikes Syedza Saintika Padang - Nursaid Nursaid; Ayu Gustia Ningsih; Marzni Mohamed Mokhtar (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2022)
Based on the results of observations made at Stikes Syedza Saintika Padang, it is known that the implementation of e-learning is not smooth both in terms of personal, infrastructure, and implementation of the learning process used. The research objective was to determine the extent to which e-learning was applied in terms of context, input, process and product. The type of research used is descriptive evaluative with a quantitative-qualitative approach. The evaluation model used is the CIPP (Context, Input, Process and Product) evaluation model. The research was conducted at Stikes Syedza Saintika Padang with 10 lecturer respondents and 68 students using purposive sampling. The results showed that the score obtained by the lecturer was in the medium category and reached a percentage of 71.2%, with details: (1) 65.5% context aspects, (2) 81.3% input aspects, (3) 66.3% process aspects, (4) 72.0% product aspects. While the scores obtained by students were included in the medium category and reached a percentage of 75.93%, with details: (1) 69.60% context aspects, (2) 79, 70% input aspects, (3) 79, 50% process aspects, (4) 74.90% of product aspects. The suggestions given by researchers, in using e-learning should be optimized from all personnel involved in the application of e-learning.